PERBEDAAN PERILAKU IBU SEBELUM DAN SESUDAH DIBERIKAN VIDEO EDUKASI CARA MENURUNKAN SUHU TUBUH BAYI PASCA IMUNISASI DENGAN PERAWATAN METODE KANGGURU - Ary Wiracani, Ida Ayu; Ayu Novya Dewi, I Gusti Agung; Widyaningtyas, Listina Ade (ARCHIVE OF COMMUNITY HEALTH; Vol 10 No 3 (2023): Desember 2023DO - 10.24843/ACH.2023.v10.i03.p06, 2023)
ABSTRACT Fever is most frequent symptom children checkedinto Puskesmas. Kangaroo treatment method (FMD) is one method of reducing fever in infants, but it is not yet known to many people so it needs to be given education such as through videos. The purpose of the study was to determine the differences in maternal behavior before and after being given educational videos on how to reduce the baby's body temperature after immunization with FMD at UPTD Klungkung I Health Center. Conducted with Pre-experimental research type with One-Group Pretest-Posttest Design on March-April 20-23 with purposive sampling technique. The sample was 33 mothers whose babies were scheduled for DPT/Hb/Hib immunization and measles, Data collection with questionnaires and check list. By univariate analysis, 81.8% of respondents aged 20-35 years with most having a college education, working as an IRT and having one child. Bivariate analysis using the Wilcoxon test. The results of the study obtained all p values < ? (0.05), so it was concluded that there were differences in maternal behavior before and after being given educational videos. Mothers of infants are expected to actively seek FMD information and health workers are expected to be able to study FMD information media. Keywords: Fever; Kangaroo Mother Care; Behavior; Educational Videos.